PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR SISWA - Ester Sandrestika (UNIB Press, 2022)
This study was conducted to increase students participation and learning achievement on English subject for eleventh grade students and to describe the effectiveness of cooperative learning Think Pair and Share in improving students achievement. The research design used was classroom action research and quasi-experimental research. The population of this study was the 11th grade students of SMK Negeri 2 Pagar Alam Academic Year 2021/2022. The sample for the classroom action research was the eleventh grade students majoring in hospitality 2 (XI AP2). The sample for quasi-experimental research was 11th grade students majoring in office management automation (XI OTKP2) and the sample for control class was the 11th grade students majoring in hospitality 1 (XI AP1). The research instrument used was observation sheets and tests. The research data then were analyzed using descriptive statistics, mean, percentage and t-test. The result of the study show that the application of cooperative learning model Think Pair and Share could increase students’ participation and learning achievement and the application of cooperative learning model Think Pair and Share is effective in improving students achievement of the eleventh grade students of SMK Negeri 2 Pagar Alam.